Negative Correlation between Outdoor Cycling Physical Activity and Depression Levels during the Covid-19 Pandemic among Members of Malang Cycling Community - Raharjo, Slamet; Kurniawan, Ari Wibowo; Handayani, Heni Yuli; Widiastuti, Widiastuti; Taufik, Muhammad Syamsul; Sandryawan, Avryan; Andiana, Olivia (Physical Education Theory and Methodology, 2022)
The purpose of the study is to analyze the relationship between the habit of outdoor cycling activities and the level of depression during the COVID-19 pandemic among the members of the bicycle community in Malang City. Materials and methods. This research is correlational, with a cross-sectional study approach. A total of 125 subjects from the bicycle community in Malang City voluntarily participated to become respondents in this study. The measurement of cycling physical activity habits was carried out using the International Physical Activity Questionnaire (IPAQ), while the measurement of the level of depression used the Hamilton Depression Rating Scale (HDRS). Measurements of physical activity habits and depression levels were performed at the same time. The data analysis used the Pearson product-moment model using statistical software package for social science (SPSS) version 17.0 with a set significance level (p ≤ 0.05). Results. The results showed that there was a negative correlation between the habit of outdoor cycling activities and the level of depression (r = –0.604; p ≤ 0.001) and showed a strong correlation between the two variables. Conclusions. Based on the results of the study, there is a negative correlation between the habit of outdoor cycling activities and the level of depression during the COVID-19 pandemic among the members of the bicycle community in Malang City.